The Role of Internal Organizational Communication in Improving Employee Performance at the Secretariat of the Water Resources Management Agency (PSDA), Lampung Province - Intannia Gracelia Effendy; Achmadi; Immawati Asniar (Journal of Creative Power and Ambition (JCPA), 2026)
This study explores how internal organizational communication influences employee performance at the Secretariat of the Water Resources Management Agency (PSDA) in Lampung Province. In public sector organizations, effective communication is essential for ensuring coordination, clarity of responsibilities, and smooth implementation of administrative tasks. Nevertheless, bureaucratic structures often create communication constraints, particularly in the flow of information across hierarchical levels. A qualitative descriptive approach was employed in this research. Data were gathered through in-depth interviews, observation, and documentation involving selected informants within the PSDA Secretariat. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that communication within the organization operates through vertical channels between superiors and subordinates, horizontal interaction among employees, and informal communication practices that help support coordination in daily work processes. Despite these communication patterns, several challenges were identified, including delayed information dissemination, limited feedback mechanisms, and structural constraints within the bureaucratic system. The study concludes that strengthening internal communication practices is crucial for improving employee performance in local government institutions. The results highlight the importance of improving information flow and coordination systems to enhance organizational effectiveness in the public sector